Aging and Thermal Conditioning of Modified Heat Exchanger Surfaces—Impact on Crystallization Fouling. Issue 7 (24th May 2017) - Siebeneck, Karl; Lüken, Johannes; Lu, Yan; Bialuch, Ingmar; Stein, Christian; Augustin, Wolfgang; Scholl, Stephan
ABSTRACT: In many research studies diamond-like-carbon coatings are used to change the wetting behavior by varying the solids´ surface free energy of heat exchanger surfaces to mitigate crystallization fouling. For future industrial application, the stability of their specific surface properties, exposed to fluidic, thermal, and chemical stresses, determines their efficiency. Therefore, fluidic thermal and cleaning stresses applied to the coating are investigated. Cleaning procedures with acid, base, and heat treatment over multiple cycles were conducted in order to investigate the solids´ surface free energy over time and thereby the stability of the coating. From this information an optimal conditioning to set constant surface properties was derived. Furthermore, the fouling behavior of CaSO4 on new and conditioned coatings was investigated in order to identify repeatable and favorable surface properties for fouling reduction. For all coatings the cleaning treatments and fouling experiments provided changes in the energetic surface properties, dominated by the change of polar/γ − content. Most probably these changes originate from varying elementary composition and structure of the coating.